THE FLAVONOID CONSTITUNTS OF LEUCAENA LEUCOCEPHALA. GROWING IN EGYPT, AND THEIR BIOLOGICAL ACTIVITY. - Hassan, Rasmia Ali; Tawfik, Wafaa Abdel-Monaem; Abou-Setta, Lubna Mohamed (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
Background: Leucaena leucocephala is native to Southern Mexico and Northern Central America, but is now naturalized throughout the tropics. The phyto-chemical data of L. leucocephala revealed the presence of terpenes, flavonoids, coumarins and sterols. Various parts of L. leucocephala have been reported to have medicinal properties. Materials and Methods: Flavonoids were isolated from the aerial parts of L. leucocephala. Antioxidant activity of the extracts and the isolated compounds was evaluated using (DPPH), as well as their cytotoxic activity using a single tumor [Ehrlish ascites carcinoma cells]. Results: The flavonoidal constituents isolated from chloroform, ethyl acetate and n-butanol fractions of the aqueous alcoholic extract of aerial parts of Leucaena leucocephala were identified as Caffeic acid, Isorhamnetin, Chrysoeriol, Isorhamnetin 3-O-galactoside, Kaempferol-3-O-rubinoside, Quercetin-3-O-rhamnoside and Luteolin-7-glucoside. Chemical structures of the isolated compounds were identified by TLC, PC and spectral techniques (UV, 1H -NMR and MS). The ethyl acetate fraction and the isolated flavonoidal compounds showed high antioxidant activity compared to Trolox (standard antioxidant compound). The different fractions and isolated compounds of Leucaena leucocephala exhibited no cytotoxic activity against Ehrlich- ascitis carcinoma cell line at the tested concentrations. Conclusion: This is the first record of the flavonoids in the aerial parts of Leucaena leucocephala (L.) except Quercetin-3-O-rhamnoside.